Pengaruh Edukasi Kesehatan Prakonsepsi dengan Animasi Terhadap Pengetahuan Catin Tentang Persiapan Kehamilan Sehat - Atikah Sulastri; Megayana Yessy Maretta; Erlyn Hapsari (Sekolah Tinggi Ilmu Kesehatan Akbidyo, 2022)
ABSTRACT Background: Anemia, chronic energy deficiency (CED), intrapartum bleeding, and low birth weight (LBW) are complications that can be experienced by mothers and babies due to inadequate preparation for pregnancy during the preconception period. Good knowledge about pregnancy preparation will encourage expectant mothers to make efforts to optimize health during the preconception period, namely the period before pregnancy. The bride and groom candidates are expectant mothers who should have good knowledge about preparing for a healthy pregnancy. Education that utilizes animated media is an effective way to increase the knowledge of the bride and groom candidates about preparing for a healthy pregnancy. This study aims to determine the effect of preconceptional health education with animation on the knowledge of bride and groom candidate about healthy preparation for pregnancy. The research was conducted on 72 bride and groom candidates at the Cihara Health Center, Lebak Regency, Banten in May-July 2022. Methode: This type of research was a quantitative design with a pretest posttest design with a control group. Data analysis used the Wilcoxon and Mann Whitney tests. The results showed that there was a significant difference in knowledge between the two groups with a value of p = 0.000. All respondents (100%) in the experimental group had good knowledge after being given education with animation, while in the control group, respondents who had good knowledge after education were 33.3%. Conclusion: The conclusion of this study is that preconceptional health education with animation is effective in increasing the knowledge of bride and groom candidate about preparing for a healthy pregnancy. Keywords: Education, Animation, Bride and Groom Candidate